Highly Efficient and Non-Precious Metal for the Li-SOCl2 Battery Using Nitrogen Doped Carbon Supported Cu Nanoparticles. Issue 4 (1st January 2019) - Du, Chao; Guan, Yongji; Liu, Shimin; Ni, Wenpeng; Pei, Junjie; Zhang, Wei; Zhang, Xiaoping; Deng, Youquan
Abstract : For lithium thionyl chloride batteries, the catalytic activity of the cathode material plays a crucial role in its electrochemical performance. In this paper, a poly (1-vinyl-3-methylimidazolium dicyanamide) ionic liquid (PIL) is selected as precursor to support CuO nanoparticles, and an efficient, non-precious metal nitrogen doped carbon supported Cu nanoparticles (N-C@Cu) composite material is designed and prepared for the lithium thionyl chloride battery cathode catalyst. X-ray diffraction (XRD) and high-resolution transmission electron microscope (HRTEM) verified that the supported CuO nanoparticles is reduced to Cu via carbon which formed from the thermally decompose of PIL. X-ray photoelectron spectroscopy (XPS) images confirm the existence of nitrogen doped carbon and Cu nanoparticles. Raman spectroscopy also demonstrate that the interaction between Cu and N-C provides more active sites. The N-C@Cu composite catalyst exhibits excellent activity in the reduction process of thionyl chloride, as can be seen from the materials display characteristics of lower discharge over-potential, and improved electron transfer of its rate-determining step. The rate performance, operating voltage and discharge capacity are all improved.